Penerapan 5s Pada Lembaga Pelayanan Publik Untuk Meningkatkan Kualitas Pelayanan - Welly Sugianto; Bobby Mandala Putra (LPPM Universitas Putera Batam, 2022)
This community service is carried out with a community target development scheme and is carried out in a village. The performance of the kelurahan is considered to be still not effective, efficient and of good quality. This happens because of low productivity, low efficiency and effectiveness. One of the causes of low productivity is an inefficient workplace. An untidy workplace creates non value added activity. Almost every day there is almost overtime due to unfinished work. Some of the unfinished activities are non value added activities. The work process is still not well documented so there is no standardization. The solution given is to increase productivity by using 5S. Several things were carried out, among others, namely coaching all sub-district staff regarding the importance of increasing productivity so that organizations can improve the quality of their services, coaching on methods and steps for implementing 5S as well as the benefits derived from implementing 5S and making 5S a culture that is inherent in every individual. Each 5S activity has guidelines or steps that must be carried out so that 5S is achieved properly. The general benefits that will be achieved are compliance with SOPs, increased discipline and staff morale, kaizen mentality is embedded in the souls of staff, staff performs all SOPs well and increases operational effectiveness through a better workplace environment.